Girls, women, and crime : selected readings - Chesney-Lind, Meda; Pasko, Lisa (SAGE, 2013)
Edited by Meda Chesney-Lind and Lisa Pasko, Girls, Women and Crime: Selected Readings, Second Edition is a compilation of journal articles on the female offender written by leading researchers in the field of criminology and women's studies. The individual sections in the book survey four major areas: theories of female criminality, literature on female juvenile delinquents, women as offenders and women in prison. The readings in Girls, Women, and Crime focus on two central questions: How does gender matter in crime and the justice system? What characterizes women's and girls' pathway to crime? In answering these key questions, the contributors reveal the complex worlds females in the criminal justice system must often negotiate-worlds that are frequently riddled with violence, victimization, discrimination, and economic marginalization.